Pengembangan Desain Kontrol Pneumatik Sistem Modular Untuk Mengatasi Sinyal Konflik - Simon Ka’ka (Politeknik Negeri Ujung Pandang, 2008)
This research design is aimed to: 1. Overcome the conflict signals on memory valve 5/2-way that may affect the piston motion. 2. Create motion of piston cylinder according to motion notation: A+ A- B+ B- . The method that used to solve problem is known “Modular System” module. The work principle of this Modular system is adjusting input signals from sensors S1, S2, S3 and S4 and then to output solenoid actuator Y1 and Y2 with referred to preparing and eliminating signals. Adjusting of signls send be done by relays with it each contactors such as normally open (NO) or Normally Close (NC). To result of piston cylinders motion above, are needed elevent relays which change signal processing from sensors to solenoid actuator. The signals from modular system will be sent to SET position Y and return spring as RESET position of the valve 5/2-way with signal conditioning that non-conflict more. Research revealed that conflict signals did not occur more in the last valve control , This was proven by: a. There were not any signals at the valve 5/2 in position SET (Y = 1) and in position RESET (return Spring = not active). b. There was an action of actuator in the work cylinder with an out-in movement without obstacle more. It was then concluded that conflict signal on memory valve 5/2-way can be coped with by a modular system process so that piston cylinder motion with notation: A+ A- B+ B- can be reached.